The Development of Augmented Reality Based Science Learning Media on Water Cycle Material for Grade V Elementary School - Eliya Rochmah; Alifsyam Islamulmuflikhun; Nugraha Permana Putra (Universitas Pendidikan Ganesha, 2025)
The limited use of interactive technology in science learning and the reliance on media that accommodate only a single learning style result in low student motivation and insufficient conceptual understanding. These challenges highlight the need for innovative multimedia learning tools that can offer immersive and adaptive learning experiences. This study aims to analyze, develop, and evaluate the feasibility of an Augmented Reality (AR) based learning media for elementary science education, as well as to examine user responses after implementing the media. The research employed a Research and Development (R&D) approach using the ADDIE model, restricted to the implementation stage. The study involved nine fifth-grade students in a small-scale trial. Data were collected through expert validation, questionnaires, interviews, and documentation, and were analyzed using qualitative descriptive and quantitative techniques. The findings indicate that the AR-based learning media is highly feasible, supported by a material expert validation score of 95.80% and a media expert score of 97.65%. User responses also fall into the excellent category with a score of 92.59%. Conceptually, the results demonstrate that integrating Augmented Reality can enhance students’ motivation, engagement, and conceptual understanding in science learning. The study implies the importance of incorporating immersive interactive technologies into learning processes and encourages the development of similar media for broader educational contexts.